Apparent diffusion coefficient values in peripheral and transition zones of the prostate: Comparison between normal and malignant prostatic tissues and correlation with histologic grade - Tamada, Tsutomu; Sone, Teruki; Jo, Yoshimasa; Toshimitsu, Shinya; Yamashita, Takenori; Yamamoto, Akira; Tanimoto, Daigo; Ito, Katsuyoshi (Journal of magnetic resonance imaging, 2008)
Purpose To investigate the utility of apparent diffusion coefficient (ADC) values for discriminating tumor in patients with prostate cancer from normal prostatic tissues in healthy adult men, and to identify correlations between ADC and histologic grade of prostate cancer. Materials and Methods A total of 125 healthy male volunteers (mean age, 60 years; range, 50–86 years) and 90 prostate cancer patients (mean age, 71 years; range, 51–88 years) underwent diffusion‐weighted imaging (DWI) of the prostate with a single‐shot echo‐planar imaging sequence using b‐factors of 0 and 800 sec/mm2. ADC was measured from two locations in the peripheral zone (PZ) and two locations in the central gland (CG) in normal subjects, and tumor locations of PZ or transition zone (TZ) in patients with prostate cancer. Results Mean ADC values of tumor regions in both PZ (1.02 ± 0.25 × 10−3 mm2/sec) and TZ (0.94 ± 0.21 × 10−3 mm2/sec) were significantly lower than those in the corresponding normal regions (1.80 ± 0.27 × 10−3 mm2/sec and 1.34 ± 0.14 × 10−3 mm2/sec, respectively) (P < 0.0001 each). Furthermore, a significant negative correlation was identified between ADC in PZ cancer and tumor Gleason score (ρ = −0.497, P < 0.0001). Conclusion ADC values appear to provide acceptable diagnostic accuracy in both PZ and TZ. J. Magn. Reson. Imaging 2008;28:720–726. © 2008 Wiley‐Liss, Inc.